Investigating the stability of the yield strength of the friction stir welding joint of similar amorphous thermoplastic based on the Ordered Weighted Averaging operators - N. Sadeghian; A.R. Chaji (مهندسی مکانیک شریف)
This paper presents an investigation of the yield strength of welded ABS thermoplastics. Welding is carried out using a steel tool mounted on a milling machine. The pin of the tools consists of cylindrical and conical profiles. Due to frictional heat and severe displacement, fusion weld occurs. Welding experimentation was designed by using the DoE theorem and welded in a universal milling machine. Significant factors of the welding process and their levels were obtained during pretests, and then weld runs were carried out successfully. Each weld bead was divided into three zones, and sampling was taken from them. The tensile strength of the welded joint is considered as a response to the process. ASTM D638 for plastics tensile test method sample preparation defined and type IV test coupons cut and installed on tensile test machine. Results were taken through standard tensile tests and analyzed using the ordered weighting average technique. Besides studying the improvement of the joint and determining optimal conditions of input parameters of the welding process, one could evaluate the stability of the response. For this purpose, an analytical approach to risk assessment is employed, which is based on the weighting of ordered input variables. The obtained results are presented in both qualitative and quantitative graphs. The Focus is on the quality of stability of response followed by workability and acceptance of the process as an industrialization method. In the current article, attention to high orness and the goal of stabilizing the maximum yield strength of the joint is achieved by selecting high levels of the aspect ratio of diameters and linear velocities with medium levels of rotational speed as well as low levels of the tilt angle of the tool. Conical tools lead to the most stable joint with a 10% variation on the weld line (for run #20) and the most strengthened one with an 18% variation on the weld line (for run #30) with 80% and 100% efficiency compared to the base material, respectively.